Revitalizing Local Wisdom of Turi-Turian Folklore as a Reflection of the Angkola Ethnic Group - Yusni Khairul Amri; Erikson Saragih; Bambang Panca Syahputra (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2021)
The 'turi-turian' folklore is assumed to be a bedtime story for children. Folklore has an essential message as an implied message for the reader or listener. Folklore is the ethnic creativity of traditional communities that maintains the culture and is firm in living traditions that are passed down from generation to generation. This study aims to highlight the local wisdom of the Sipirok tribal community through its folklore. This research uses qualitative research methods with ethnographic design, which includes data collection of folklore texts, data presentation, and drawing conclusions or verification. The data of this research is sourced from the analysis of data from Angkola folklore collected in the book ‘Turi-turn Nihalak Angkola Banggo-banggo’. This research reveals that folklore texts have a wealth of philosophical values that reflect the characteristics of indigenous peoples that have existed from the past until now which are still maintained as wisdom that is still upheld by indigenous communities. As one of the intangible assets of the Angkola Sipirok community, which has an ethnic culture, it is reflected in the characteristics of the Angkola Sipirok indigenous people who teach values as local wisdom. Based on the data analysis of the Sipirok ‘Turi-turian’ folklore, several local pearls of wisdom were found: persistence, hard work, deliberation, cooperation, social spirit, and willingness to help.